A TRANSFORMATIONAL LEADERSHIP MODEL IN SUSTAINABLE PRIMARY SCHOOL ADMINISTRATION - Boonklum, Ruchanee; Utairat, Weerawat (Journal of MCU Nakhondhat, 2020)
The objectives of this research were to determine and assess the pattern of using the state transformation leaders in a sustainable primary school administration. The target group used in this research totaled 798 primary schools under the Office of the Basic Education Commission in Bangkok and perimeter. The research instruments comprised questionnaires, interview forms and assessments of component validity, focus group and the assessment pattern. The statistics for data analysis comprised mean, standard deviation, multiple regression analysis and content analysis. 1) The results of the research showed that first, the transformational leadership of the primary school principals was at a high level overall and the data were less fragmented. When considered in each aspect, the transformational leadership was found at a high level in all aspects, including motivation, strong team building, creating an idealistic vision and cognitive stimulation in rank. 2) The administration of primary schools for sustainability in student development was at a high level overall and the data were less fragmented. When considering each aspect, the school administration was sustainable in the development of learners at a high level in all aspects including teaching management, development of internal quality assurance systems, curriculum development and evaluation in rank. 3) The administration of primary schools created an idealistic vision, cognitive stimulation and strong team building of a leader who uses power to influence the administration of primary schools for sustainability in student development. 4) The two components of transformational leadership in elementary school administration to ensure sustainability in student development consisted of strong team building and ideological vision and intellectual stimulation. 5) The pattern of using transformational leadership in sustainable primary school administration was a set of principles, i.e., tolerable, reasoning and good immunity. The process of using transformational leadership in primary school administration aimed to enable the learners to acquire desirable characteristics according to the sustainable goals of the school. This was according to the goal of implementing transformational leadership step by step.